The Role of Macro-Prudential Policies in the Boom and Adjustment Phase of the Credit Cycle in Estonia - Sutt, Andres; Korju, Helen; Siibak, Kadri (2012)
The Estonian economy experienced an unusually long business and credit cycle during the first decade of the 21st century. The magnitude of the cycle tested what can be achieved by traditional policy tools and the limits of macro-prudential policies. The country's financial sector, almost fully consisting of foreign banks, displayed the complexities of cross-border regulation and supervision. Capital and liquidity requirements that were stricter than international minimums, as well as the build-up of fiscal buffers, were instrumental to engineering an orderly adjustment. Openness and integration, including well-advanced cross-border cooperation, were equally important in maintaining financial stability throughout the global financial crisis.